Searching for meaning: A grounded theory of family resilience in adult ICU. Issue 5 (11th October 2018) - Wong, Pauline; Liamputtong, Pranee; Koch, Susan; Rawson, Helen
Abstract: Aim: To explore families' experiences of their interactions in an Australian adult intensive care unit (ICU) to develop a grounded theory that can be used by critical care nurses to improve patient‐ and family‐centred care (PFCC). Background: Families in ICU play an important role in the patient's recovery and outcomes. However, families are at risk of significant psychological morbidity due to their experiences in ICU. Although many ICU patients can make their own decisions, a large proportion are unconscious or chemically sedated and unable to contribute to decisions about their care, leaving the decision‐making role to the family. Therefore, the families' psychosocial and emotional well‐being must be supported by implementing evidence‐based interventions that align with a PFCC approach. This study describes the findings of a grounded theory of family resilience in ICU, of which the core category is Regaining control . The focus of this paper is on the major category: Searching for meaning . Methods: We adopted a constructivist grounded theory method. Twenty‐five adult family members ( n  = 25) of 21 patients admitted unexpectedly to an ICU in metropolitan Australia were recruited. In‐depth interviews were used to collect the data, and the analytical processes of constructivist grounded theory underpinned the development of a core category and related subcategories. Results: When adult family members experience the unexpected admission of a relative to ICU, they move towards a state of being beyond emotional adversity and regaining control when facilitated to search for meaning in their situation. When families were able to make sense of their situation and find a purpose by contributing to their relative's recovery, it encouraged them to cope and be resilient. Conclusions: Our findings can be used to promote PFCC in ICU, which considers a collaborative approach to meet the patient's needs while providing emotional and psychosocial support to their families.